Impact of Changes in Jakarta's Status on West Java Province: The Ecology of Public Administration and Utilitarianism Perspective - Unpad, Bonti; Bekti, Herijanto; Nurasa, Heru; Jawan, Jayum Anak; Pancasilawan, Ramadhan (Jurnal Manajemen Pelayanan Publik, 2024)
This research explains the reality of moving the capital city of Indonesia from Jakarta to Ibu Kota Nusantara (IKN) in North Penajam Paser, East Kalimantan Province, and the opportunities for the dynamics of ecological balance in public administration that will be formed for West Java Province using the equilibrium model from Fred W. Riggs. The previous research has not yet found publications on IKN using the ecological perspective of public administration and utilitarianism. Reserachers uses qualitative research methods uses prospective case studies as a form of research. The research results show that there will be a change in equilibrium in the public administration system. The policies produced by the political system in the form of moving the country's capital from DKI Jakarta to IKN, changing DKI Jakarta to DKJ, and expanding the agglomeration area are predicted to shift the ecological balance of West Java Province's public administration. Viewed from the perspective of Jeremy Bentham's pleasure and pain utilitarianism, the West Java Provincial Government can take a development policy direction that is based on the reality of human resource conditions and geographical advantages.